Analisis Kesalahan Berbahasa dalam Penulisan Autobiografi Para Mahasiswa Prodi S-1 Statistika FMIPA Unimus Angkatan 2016 - Mujid Farihul Amin (Program Studi Sastra Indonesia, Fakultas Ilmu Budaya, Universitas Diponegoro, 2017)
Language errors in the writing of autobiography conducted by the students of S-1 Program Statistics FMIPA Unimus can be grouped into errors from the point of writing / spelling and errors from the point of grammar. Spelling mistakes include prepositional and affixed writing errors, capital letter writing, abbreviation, and numerical errors. Grammatical errors include fragmentary sentences, confusing sentences, sentences with predictions of transitive active verbs but not directly followed by objects, and unclear sentences of the subject.